The Relationship Between Self-Concept and Entrepreneurial Interest of Entrepreneurship Training Graduates at PKBM Karang Putih - Dwi Adha, Putri; Solfema, Solfema (Universitas Negeri Padang, 2024)
This research was motivated by the low interest in entrepreneurship from entrepreneurship training graduates at PKBM Karang Putih, which was thought to be due to the low self-concept of entrepreneurship training graduates. This research aims to see a picture of the self-concept of entrepreneurship training graduates, a picture of entrepreneurship training graduates' interest in entrepreneurship at PKBM Karang Putih, the relationship between self-concept and entrepreneurship interest of entrepreneurship training graduates at PKBM Karang Putih.This research uses a quantitative approach with a correlational type. The population in this study were all entrepreneurship training graduates at PKBM Karang Putih, totaling 75 people with a sample of 60% (45). The sampling technique used is Cluster Random Sampling and the data analysis technique uses percentage and product moment formulas.The results of this research show that the self-concept of entrepreneurship training graduates is not yet of high quality and the interest in entrepreneurship of entrepreneurship training graduates is low, and there is a significant relationship between self-concept and interest in entrepreneurship and entrepreneurship training graduates at PKBM Karang Putih. It is recommended that: (1) Entrepreneurship training graduates are expected to understand the importance of having a self-concept and interest in entrepreneurship (2) Institutions can provide training or materials regarding the importance of a positive self-concept Keywords: Self-concept, Interest in entrepreneurship